THE STUDENTS’ CHALLENGES IN SPOKEN ENGLISH PROFICIENCY: A CASE STUDY IN AN INDONESIAN UNIVERSITY - Jalaluddin; Indri Dayana (SILABUS: Jurnal Ilmu dan Inovasi Pendidikan, 2025)
This study investigates challenges faced by 5th-semester English major students at an Indonesian university in developing proficient English-speaking skills. Utilizing a qualitative descriptive method, the research aims to identify and analyze impediments hindering students' spoken English proficiency. Subjects were 5th-semester English major students, and data collection involved observation, interviews, and documentation. The findings reveal diverse challenges, including low vocabulary mastery, grammar deficiencies, pronunciation difficulties, fear of judgment, lack of confidence, limited practice opportunities, minimal exposure to English, environmental factors, mother tongue dominance, low motivation, and ineffective teaching strategies. Pronunciation emerged as the predominant issue, with students expressing apprehension due to fear of mispronunciation. This research provides valuable insights for educators, curriculum developers, and language learning practitioners, offering a nuanced understanding of specific areas requiring attention. Addressing these challenges can inform targeted interventions and strategies, fostering an improved learning environment for enhancing English-speaking skills.